PERANCANGAN INTELLECTUAL PROPERTY KARAKTER PUTRI AJI BERDARAH PUTIH DALAM GAYA POPKULTUR UNTUK REMAJA DI INDONESIA - Keefe Chance Kartika; Aditya Nirwana; Ayyub Anshari Sukmaraga (Ma Chung Press, Universitas Ma Chung, 2026)
The development of intellectual property (IP) plays a strategic role in driving the growth of Indonesia’s innovation based creative industry. Although local IP holds significant potential, its contribution remains behind that of foreign IP, particularly in the animation and creative products sectors. One of the main challenges is the limited integration of local cultural narratives into contemporary media formats that resonate with youth interests. The folk tale “Putri Aji Berdarah Putih” represents an oral cultural heritage from East Kalimantan that has yet to gain widespread recognition due to constraints in documentation and visual representation. This study aims to design an IP character based on the legend of Putri Aji by applying character design and 3D modeling as the primary media. The 3D model is employed to present the character’s visual form concretely (especially in the form of figurines) and is supported by supplementary media such as illustrations and an artbook. This strategy seeks to reintroduce Indonesian folklore through visual approaches that align with the preferences of teenagers, who tend to be attracted to visual content and interactive media.